Jarcho-Levin Syndrome: Two Consecutive Cases in the Same Family - patsouras grigorios; George Maroudias; Saloum Ioannis; Patsouras Konstantinos (Tehran University of Medical Sciences, 2020)
Jarcho-Levin Syndrome was first defined in 1938 by Saul Jarcho and Paul Levin. In the medical literature Jarcho-Levin Syndrome has a variety of synonyms such as Spondylocostal dysplasia/Dysostosis, Spondylocostal Dysostosis (SCD), Spondylothoracic dysplasia/Dysostosis and costovertebral dysplasia. For years the SCD and a similar disorder, spondylothoracic dysplasia, were considered the same disorder and referred as Jarcho-Levin Syndrome. Today we know that these two disorders are different clinical entities with different causes and that the term Jarcho-Levin Syndrome should be reserved for individuals with Spondylocostal dysplasia. Affected individuals with SCD have various abnormalities in the development of the spine and ribs. Due to these abnormalities they are more prone to develop thoracic insufficiency syndrome which may eventually lead to early neonatal death. In the current case report we describe two consecutive cases with SCD in the same family. In the case of a strong clinical suspicion from the findings of the ultrasound scan we should proceed to a molecular genetic diagnosis of a mutation in DLL3, MESP2, LFNG and HES7 gene by sequencing the entire coding area of the fetal Deoxyribonucleic acid (DNA).